Recent Advances in Non-Sugar Components of Sugarcane Juice: A Review. - FANG, KUN; LI, PEI; HUANG, XIANGRUI; LI, YIHAN; WANG, HANBING (Current Research in Nutrition & Food Science, 2026)
As the global economy booms, the quality of refined sugar and its derivatives is attracting increasing attention. Mixed juice extracted from sugarcane contains many impurities other than sucrose, such as pigments, nitrogenous substances, organic acids, colloidal substances, lipids, and inorganic substances. Although some of these impurities (e.g., amino acids, vitamins, flavonoids, and minerals) are beneficial to human health, they degrade the quality of sugar and its derivatives, affecting their production and utilization. Understanding the non-sugar components and colored substances in sugarcane juice mixtures is essential to ensure product quality, prolong the storage period, and improve the organoleptic properties. This review summarizes the non-sugar components of sugarcane juice, including their composition, chemical structures, and contents. Additionally, it highlights four colored substances (natural pigments, melanoidins, caramels, and hexose alkaline degradation products) in sugarcane juice and their formation mechanisms.